Financeirização e gestão da qualidade: estudo de caso em uma empresa de autopeças - Cresce, Liana Fernandes de Azevedo de (2013)
From Fordism, we see that the different ways of thinking about organizational objectives influenced the organization of work in factories, and in parallel, quality management has also kept pace with changes in those goals. The increased complexity of products, among other factors, requires greater sophistication of quality from the 50's. This increased complexity makes the quality so far focused exclusively on conformance to specifications, within their factories, pass to cover the use of the product design, involving all departments of the company. Currently, the ultimate goal of corporations is to deliver shareholder value, generating changes in organizations. Through a case study, this paper aims to explore the influence of financialization in quality management. The research was conducted in an auto-part industry whose recent history is marked by the acquisition process by a multinational company controlled by a U.S. investment.